THEORETICAL AND METHODOLOGICAL APPROACH TO THE FORMATION OF THE STATE POLICY PRINCIPLES SYSTEM OF E-DEMOCRACY TAKING INTO ACCOUNT THE INTERNATIONAL EXPERIENCE AND THE DEVELOPMENT FEATURES OF UKRAINE - Yansons , Y.; Semenchenko , A. (Theory and Practice of Public Administration, 2020)
Aspects of the theoretical and methodological foundations of state policy in the field of formation, development and implementation of e-democracy have been discussed in the article. The analysis focuses on the principles of e-democracy as the basis for laws of a doctrinal, conceptual and strategic level. At the stage of problem formation, the creation of such bases requires a science-based approach has been indicated. A similar approach combines international experience and national characteristics of the democratic institutions development in a particular state. These features include organizational and technical, economic, political, historical, educational and cultural, legislative etc. These features differ in the nature and scale of their influence due to their essential attributes. At the same time, each of the features has its own specific impact on the e-democracy development and consists of a combination of elementary components. The influence vector of these features can radically differ from each other, namely, it can be inhibitory, accelerating or neutral (without affecting). A theoretical and methodological approach to the formation of many basic principles of e-democracy has been developed, based on the results of the research. The developed approach is based on expert determination of the influence degree of the principles on democratization processes, taking into account the particular development of a particular country and the best international experience. Along with this, a methodology has been developed for ranking and selecting principles into many basic principles, depending on the degree of their influence on the effectiveness of state policy in the e-democracy formation and implementation. The tools and mechanisms of e-democracy are formed and applied based on these principles. Among other things, a comparative analysis of the totality of the e-democracy principles, as defined in the Recommendations of the Council of Europe Committee of Ministers CM/Rec (2009)1 to the Council of Europe member states on the development of e-democracy and the Concept for the e-democracy development in Ukraine has been carried out. This analysis has been conducted; with a view to their conformity and taking into account the peculiarities of Ukraine’s development. The analysis showed that the list of principles presented in the concept of the e-democracy development in Ukraine is based on the set of principles from Recommendations CM/Rec (2009)1, but does not take into account the development features of Ukraine. The scope of further research is determined in the direction of an in-depth analysis and exploration of the factors of influence on the e-democracy development in Ukraine and the development of methodological approaches to the formation of an integrated mechanism of public administration for the development of e-democracy.